Social-structural properties and HIV prevention among young men who have sex with men in the ballroom house and independent gay family communities - Young, Lindsay E. (Soc Sci Med, 2016)
The endogenous social support systems of young Black men who have sex with men (YBMSM), like surrogate families and social networks, are considered crucial assets for HIV prevention in this population. Yet, the extent to which these social systems foster sexual health protections or risks remains unclear. We examine the networked patterns of membership in ballroom houses and independent gay families, both Black gay subcultures in the United States, and how these memberships are related to HIV protective and risk traits of members. Drawing from a population-based sample of 618 YBMSM living in Chicago between June 2013 and July 2014, we observe a suite of protective and risk traits and perform bivariate analyses to assess each of their associations with being a member of a house or family. We then present an analysis of the homophilous and heterophilous mixing on these traits that structures the patterns of house and family affiliations among members. The bivariate analyses show that members of the house and family communities were more likely than non-members to report protective traits like being aware of PrEP, having health coverage, having a primary care doctor, and discouraging sex drug use among peers. However, members were also more likely to engage in the use of sex drugs. With respect to how these traits inform specific house/family affiliations, results show that members who had a recent HIV test, who were PrEP aware, or who engaged in exchange sex were more likely to belong to the same house or family, while HIV positive individuals were less likely to cluster within houses or families. These findings provide insights regarding the strengths and vulnerabilities of the house and gay family communities that can inform more culturally specific interventions that build on the existing human and social capital in this milieu.